Morphology and activity of the Helgoland Mud Volcano in the Sorokin Trough, northern Black Sea. (January 2019) - Wu, Tingting; Sahling, Heiko; Feseker, Tomas; Rendle-Bühring, Rebecca; Wei, Jiangong; Wintersteller, Paul; Marcon, Yann; Pape, Thomas; Römer, Miriam; Bohrmann, Gerhard
Abstract: Morphological change and activity of submarine mud volcanoes (MVs) are still poorly understood. In this study, we integrated acoustic subbottom profiles, Autonomous Underwater Vehicle (AUV) high-resolution bathymetric and backscatter data, Remotely Operated Vehicle (ROV) seafloor observations, Bottom Water Temperatures (BWT), and compositions of gas samples collected from three research expeditions, to study the morphology and activity of the Helgoland mud volcano (Helgoland MV) in the Sorokin Trough of the Black Sea. Based on the micro bathymetric and backscatter maps, we conducted a geomorphological analysis which differentiates the Helgoland MV into five regions, which are: the active center, the inner crest, the inner moat, the outer crest, and an outer moat. Special seafloor features, such as gas bubble emissions, mud breccia and mud pools, were observed in different regions by ROV observations. They indicate a heterogeneous distribution of materials and activities at the Helgoland MV. Active mud extrusion from the center was inferred from BWT elevations (up to 1.652 °C) that showed the same orientation as a major fault (NW-SE) at the location. Methane stable carbon isotopes (−58.1∼−63.6‰) and molecular compositions of light hydrocarbons (C1 /C2+ = 2836, CH4 = 99.545%, C2 H6 = 0.033%, C3 H8 = 0.002%, CO2 = 0.417%) suggest a predominance of biogenic hydrocarbons with an admixture of thermogenic gas. Circular faults surrounding the Helgoland MV, as observed in the bathymetric and sub-bottom profiles, are speculated to be formed due to subsidence of the MV caldera and gravity driven sediment movement. A conceptual model is proposed to explain the interrelationship between the seafloor morphology and activity of the Helgoland MV. Combining multidisciplinary data, especially from the application of ROVs and AUVs, broaden the scope in which the activity and morphology of submarine mud volcanoes can be investigated.